Didaktische Texte im Bereich der Giottodidaktik. Versuch einer Begriffsbestimmung - Grucza, Sambor (Glottodidactica, 1999)
The aim of the article is to discuss the question of (glotto)didactic texts from the point of view of glottodidactics. The division of texts into didactic and non-didactic can be drawn according to the criteria of glottodidactic relevance of a given text. The glottodidactic relevance can be defined as the applicability of a given text for reaching an expected glottodidactic aim. Authenticity of didactic text is one that is congruous with the communication situation in which, or for which it was formulated. An original didactic text in turn is one which has not been changed in any way with respect to its original form and contents. Every didactic text must be an authentic text, but it does not necessarily have to be an original text. The characteristic feature of didactic texts may be divided into linguistic features and glottodidactic features.